Investigating the category boundaries of emotional facial expressions: Effects of individual participant and model and the stability over time. (February 2015) - Cheal, Jenna L.; Rutherford, M.D.
Highlights: We investigated the stability of categorical perception over time. The category boundary was identified for each participant for the happy–sad continuum. Participants were tested over time to determine if category boundaries are stable. Perception of faces is stable over time with a few consistent performance differences. Abstract: Emotional facial expressions are perceived categorically. Little is known about individual differences in the position of the category boundary, nor whether the category boundaries differ across stimulus continua. Similarly, little is known about whether individuals' category boundaries are stable over time. We investigated these topics in a series of experiments designed to locate category boundaries using converging evidence from identification and discrimination tasks. We compared both across individuals and within individuals across two sessions that spanned a week. Results show differences between individuals in the location of category boundaries, and suggest that these differences are stable over time. We also found differences in boundary location when we compared images depicting different models.